Accumuler du capital, accumuler du pouvoir ? - Pierre Wokuri (Revue de la Régulation)
Much research has gone into understanding the alternative dimension of cooperatives. However, few studies look into their capacity to influence power relations. Based on fieldwork on Danish wind power cooperatives, this article addresses this issue by assessing to what extent the accumulation of economic capital by these organizations has gone along with their accumulation of political power. I examine how Danish wind power cooperatives exerted power in orienting public policy from the 1970s to the late 2010s.